An evaluation of the determinants of Singapore's total fertility rate. - Tan, Yuan Mei. (2008)
This report aims to identify and evaluate the determinants of Singapore's Total Fertility Rate. In addition, the study hopes to provide recommendations to boost Singapore's TFR.